PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING BERMEDIA VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR SUBTEMA BERSYUKUR ATAS KEBERAGAMAN - Sandi Budiana; Yuli Mulyawati; Feby Melaniawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the effect of the Problem Based Learning model with learning media on learning outcomes in the sub-theme of gratitude for diversity in fourth grade students of Nenggewer 01 State Elementary School, Cibinong District, Bogor Regency. This type of research is a quasi-experimental. The population consists of classes IV-A and IV-B consisting of 58 people. The research was conducted three times in each class group. Sampling was done by simple random sampling technique. Research data were collected using a pretest and a posttest. Data analysis was carried out with the n-gain test, normality test, and homogeneity test as a prerequisite test before testing the hypothesis (t test). the results of data analysis obtained t-count (4.907) > t-table (2.0034) for a significance of 5%. Based on the test criteria, then H0 is rejected and Ha is accepted. Based on the results of these studies, it can be concluded that there is an effect of the Problem Based Learning model on learning outcomes.